Peningkatan Hasil Belajar Peserta Didik Melalui Problem Based Learning Dengan Media Mistery Box Pada Materi Pecahan Kelas IV Di SDN Keseneng - Ana Nur Soimah; Rintis Rizkia Pangestika, Arum Ratnaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Improving Student Learning Outcomes Through Problem Based Learning With Mystery Box Media On Fraction Material Of Grade IV SDN Keseneng. This study aims to: 1) Describe the application of the Problem Based Learning model with mystery box media on fraction material in improving the learning outcomes of grade IV students of SDN Keseneng, 2) Describe the improvement of student learning outcomes through the Problem Based Learning model with mystery box media on fraction material of grade IV SDN Keseneng. The study was conducted in two cycles consisting of planning, implementation, observation, and reflection. The data analysis technique used qualitative analysis techniques and quantitative analysis techniques. The results of this study indicate that the application of the Problem Based Learning model with mystery box media can improve student learning outcomes. This is evidenced by data through the learning implementation sheet in cycle I 79%, cycle II increased to 95% with a success indicator of 80% so it can be concluded that the application of the Problem Based Learning model with mystery box media can affect student learning outcomes. This is evidenced by the average pre-cycle score of 60.42, which increased to 63.75 in cycle I, and 77.08 in cycle II. This demonstrates that the application of the Problem-Based Learning model with the mystery box can improve student learning outcomes in fractions.